Web based Village Head Election Information System Using the RFID Method - Tomin; Muhammad Alfan Rosid (Universitas Muhammadiyah Sidoarjo, 2022)
Indonesia is a democratic country that holds general elections every five years. The general election is carried out starting from the village level, namely the Village Head Election (Pilkades). Pilkades are still mostly done manually when selecting candidates. The purpose of this study is to utilize more modern and more efficient technology, by using pure web-based application technology to reduce fraud and minimize unauthorized votes that often occurred in previous years. The results of the research on the proven RFID method that has been developed are functionally all features run smoothly with the black-box testing method and are compatible in various versions of Laptops and Android. Compared to manual input techniques because of the speed and accuracy in the selection and calculation of the number of voter data.